Pneumatic Coagulation-Flocculation on Domestic Wastewater Treatment - Azzahra Hanggararas Sasdika; Khusnul Khotimah Ayuningtiyas; Aulia Ulfah Farahdiba; Ayu Putri Sahitamara (Future Science)
Activities carried out in the household produce waste called Domestic Waste. Wastewater samples were taken from Penjaringan Sari Flats, Surabaya, East Java. This research is based on a literature study, namely by collecting data from previous studies. The purpose of this study was to determine the effect of the pneumatic coagulation-flocculation method for domestic wastewater treatment. After testing the characteristics of the water sample, it was found that several parameters had values ??determined by the quality standard. From this research, it is obtained. The results showed that the pneumatic coagulation system was more effective in reducing the organic load compared to mechanical and hydraulic coagulation.